From surface structures to the integral depth model of the Kirovograd ore region (Ukrainian Shield). 1 - Starostenko, V. I.; Kazansky, V. I.; Popov, N.I.; Drogitskaya, G. M.; Zayats, V. B.; Makivchuk, O. F.; Trypolsky, A. A.; Chicherov, M. V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2010)
The discovery of a middle-scale mantle trough in the Kirovograd ore district under uranium, gold and lithium deposits brought a new insight into metallogeny of the district and made it necessary to trace its surface structures to the M boundary.In this study, surface structures are described in more detales using numerous data from exploration drilling, relationships between the crustal Kirovograd-Novoukrainsk granitoid massif, mantle-related Korsun-Novomirgorod massif and M interface are discussed, surface and deep structures of uranium ore fields are correlated and vertical metasomatic and ore zonality of large uranium deposits is considered.